When Positive Emotion as a Mediator in Creating Impulse Buying at Shopping Discount Event - Dhiya'u Shidiqy; Wahyu Rusdiyanto (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
This research aims to determine the role of positive emotion as a mediator of price discounts and event marketing in creating impulse buying at the Shopee 12.12 Birthday Sale. This research is quantitative and descriptive. The population of this study was members of the Tawangsari Tulungagung Village Youth Organization (TARUNATA) who made purchases on Shopee on December 12, 2023, namely 38 people. Sample size guidelines using saturated samples, data analysis in this study using descriptive statistical techniques, and inferential statistical analysis using the SPSS 23 application. The results of this research show that price discounts are proven to affect positive emotions and are proven to affect impulse buying, both directly and through mediation. positive emotions. Meanwhile, event marketing has been proven to have a positive and significant effect on positive emotions and has been proven to affect impulse buying, both directly and indirectly. The results of this research also confirm that positive emotion is a partial mediator in influencing price discounts and event marketing in encouraging impulse buying at the Shopee 12.12 Birthday Sale.